Bioelectric activity of the visual system in trichromats and color-blinds according to visual evoked potentials to achromatic and chromatic stimuli (Ukrainian Journal of Ophthalmology, 2026)
Background. Psychophysical methods, the most known of which are polychromatic tables and spectral anomaloscope study, are used for diagnostics of color vision defects. However, all these methods are based on the subjective answers of a person, which makes it impossible to use them for certain patients. To date, there have been proposed electrophysiological methods, in particular, a recording of visual evoked potentials (VEP).  They are supposed to be of a high diagnostic value.Purpose: to study the bioelectrical activity of the visual system in normal trichromats and red and green color blinds according to visual evoked potentials in response to achromatic and chromatic stimuli.  Material and Methods. The study was performed in 17 normal trichromats, 16 red color blinds (protanopes), and 29 green color blinds (deuteranopes). The patients’ age ranged within 17-30 y/o. VEPs were recorded using a RetiScan unit (Roland Сonsult, Germany). Pattern-reversal VEPs were elicited by checkerboard stimuli with black-and-white checks and chromatic checks: red-and-black, R, red (R=255 according to the RGB color chart); green-and-black, G, green (G=200); blue-and-black, B, blue (B=255); and opponent color pairs: red-and-green (R-G) and blue-and-yellow (B-Y). The sizes of the checks used were 1° and 0°15'; reverse frequency was 1.5 Hz; and the pattern contrast was 97%. We recorded amplitudes and latencies of negative waves N75 and N135, and a positive wave P100. Results. Pattern VEP N75, Р100, and N135 latencies in response to black-and-white checkerboard with 1° and 15' checks in protanopes and deuteranopes did not differ from the norm; contrary, N75, Р100, and N135 amplitudes were less than those in normal thrichromats. To chromatic stimuli, N75 latency in persons with color vision defects was almost similar to that in normal trichromats; P100 latency to blue-and-black and red-and-green stimuli was higher than the norm, which was more common for deuteranopes than for protanopes. Generally, the latency values were higher to chromatic stimuli as compared to achromatic ones, except for response to blue-and-yellow stimuli, which were equal. P100 and N135 amplitudes to black-and-white and chromatic stimuli with check sizes 1° and 15' were less in the persons with color vision defects than in normal trichromats. N135 amplitude to black-and-white stimuli with check sizes 1° and 15' was equal to P100 amplitude both in normal trichromats and in the persons with color vision defects. To chromatic stimuli, N135 amplitude was a little higher to stimuli with check size 15' than with check size 1°.Variability coefficient of latency in response to achromatic and chromatic stimuli was 5.9% in normal trichromats, and 6.6% in protanopes and deuteranopes; variability coefficient of amplitude was 38.4% in the norm and exceeded 50% in the persons with vision color defects.Conclusions. Peculiarities of the biological activity of the visual system in red and green color blinds were revealed according to visual evoked potentials. The data obtained make it possible to consider VEP as an objective method for diagnostics of color vision defects and require the following studying.
Keywords: color vision; normal trichromacy; protanopy; deuteranopy; visual evoked potentials